Prefrontally modulated vagal neuroimmunomodulation is associated with telomere length - Ask, Torvald F.; Sütterlin, Stefan (Frontiers in Neuroscience, 2022)
Background Accumulated senescent cells are proposed to be one of the main drivers of age-related pathology such as dementia and cancer through disruption of tissue structure and function. We recently proposed the Neuro-Immuno-Senescence Integrative Model (NISIM), which relates prefrontally modulated vagal tone and subsequent balance between vagal and sympathetic input to the spleen to inflammatory responses leading to generation of reactive oxygen species and oxidative telomere damage. Aim In this study, we assess inflammation as a mediator in the relationship between prefrontally modulated vagal tone and leukocyte telomere length (LTL). We also assess the relationship between a recently proposed index of vagal neuroimmunomodulation (vagal tone/inflammation ratio; NIM index) and telomere length. Methods This study uses participant data from a large nationally representative longitudinal study since 1974 with a total of 45,000 Norwegian residents so far. A sub-sample of 131 participants from which ultrashort recordings (30 s) of vagal tone, c reactive protein, and LTL could be obtained were included in the study. Relationships were analyzed with Pearson’s correlations and hierarchical multiple linear regression using either vagal tone and CRP or the NIM index to predict telomere length. Results Vagal tone was a significant positive predictor of telomere length but this was not mediated by c reactive protein, even after controlling for confounders. The NIM index was a significant positive predictor of telomere length, also when controlling for confounders. In a follow-up analysis simultaneously comparing telomere length between groups with high and low values of vagal tone, and between groups with high and low NIM index values, telomere length was only significantly different between NIM index groups. Conclusion This is the first study suggesting that prefrontally modulated vagal neuroimmunomodulation is associated with telomere length thus supporting the NISIM. Results indicate that the NIM index is a more sensitive indicator of vagal neuroimmunomodulation than vagal tone and CRP in isolation.